2011
DOI: 10.1038/nprot.2011.301
|View full text |Cite
|
Sign up to set email alerts
|

AAV-mediated gene targeting methods for human cells

Abstract: Gene targeting with adeno-associated virus (AAV) vectors has been demonstrated in multiple human cell types, with targeting frequencies ranging from 10−5 to 10−2 per infected cell. these targeting frequencies are 1–4 logs higher than those obtained by conventional transfection or electroporation approaches. a wide variety of different types of mutations can be introduced into chromosomal loci with high fidelity and without genotoxicity. Here we provide a detailed protocol for gene targeting in human cells with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
177
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(187 citation statements)
references
References 64 publications
(78 reference statements)
5
177
0
2
Order By: Relevance
“…They were generated using recombinant adenoviral-associated (rAAV) and CRISPR/Cas9 (LIG3 −/− :LIG4 −/− line only) targeting methods, as described (Khan et al 2011;Oh et al 2014;B Ruis, T Takasugi, S Oh, EA Hendrickson, unpubl.). These cell lines represent our models of DNA repair pathways that are selectively compromised.…”
Section: Methods Cellsmentioning
confidence: 99%
“…They were generated using recombinant adenoviral-associated (rAAV) and CRISPR/Cas9 (LIG3 −/− :LIG4 −/− line only) targeting methods, as described (Khan et al 2011;Oh et al 2014;B Ruis, T Takasugi, S Oh, EA Hendrickson, unpubl.). These cell lines represent our models of DNA repair pathways that are selectively compromised.…”
Section: Methods Cellsmentioning
confidence: 99%
“…Therefore, screening the monoclonal shRNAmir-expressing cells may result in more efficient miRNA expression and targeted knockdown. Alternatively, targeted integration at a defined locus such as the AAVS1 locus (safe harbour site) may also improve miRNA expression (DeKelver et al, 2010;Khan et al, 2011). We also found that expression levels of miRNAs in tandem-shRNAmir-transduced 293T and MDCK cells were different (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…In this regard, rAAV has become increasingly popular as the most efficient tool to precisely introduce defined DNA modifications at the target site in the cellular genome with remarkably high efficiencies of up to 1% in the cell population (Hendrie & Russell, 2005;Khan et al, 2011;Russell & Hirata, 1998;Vasileva & Jessberger, 2005). Targeting efficiencies could be increased further by 60-100 fold or more by introducing a DSB at the target site with a site-specific endonuclease (Miller et al, 2003;Porteus et al, 2003).…”
Section: Raav-mediated Gene Targeting and Dna Repair Pathwaysmentioning
confidence: 99%